Psychoanalytical Review of Early Professionalization of a Personality in a Family - Virna, Zhanna (Psychological Counseling and Psychotherapy, 2021)
The paper represents the theoretical grounding of psychoanalytic determination of early professionalization of a personality in a family. The theoretical review includes the analysis of basic psychoanalytic theories and concepts that relate to the issue of early professionalization of a personality. The specificity of psychoanalytic position in the consideration of professionalization beginning from the early childhood is inseparably connected with the family relationships. The aim of the presented material is theoretical review and systematization of the main psychoanalytic positions of the study of early professionalization of a personality in a family. Based on theoretical systematization and generalization of the main psychoanalytic postulates, the following has been surveyed: the approach of the effect of a child’s unconscious desires on the choice of profession in Z. Freud’s theory; the study of operatropisms and sublimation as the basis for the formation of professional development by T. Moser; the concept of the influence of organic processes on the development of individual by E. Bordin; A. Roe’s theory of appropriateness of the attitude to the needs and orientation to the interests and dominant motives; the concept of the impact of life scenarios and strategies of the early childhood on the adult life by E. Berne, A. Bruhn, I. Stewart and V. Joines; A. Adler’s analytical theory of personality in the concepts of experiencing one’s superiority; social interest and aspiration to power in the future professional sphere; works concerning the definition of basic trust-distrust by E. Erickson and basic anxiety by K. Horney, which extend to the content of successful professionalization; the approach of unconscious desire for approval in the ego-psychology of H. Kohut; the basic positions of attachment theory of J. Bowlby; D. Winnicott’s transitional space, M. Mahler’s separation-individuationl; R. Spitz’s anaclitic depression; preverbal consciousness of D. Stern. Based on the analysis and theoretical generalization of the problem, it is stated that unconscious children’s impulses and ways to protect against them in a family upbringing compose the basis of personality disorders, the symptoms of which explain subjective sufferings, doubt and uncertainty in adult professional life.